Studies on the Pathogenicity of Tetrameres Mohtedai and acuaria Spiralis of Fowl - Ramaswamy K (Department of Parasitology, College of Veterinary and Animal Sciences, 1977)
Controlled experiments were conducted at three levels of monospecific and dispecific infections with two commonly occurring spirurid worms of fowls viz. Tetrameres mohtedai and Acuaria spiralis. The blood studies conducted in monospecific T. mohtedai infection revealed a normocytic normochromic anaemia and eosinophilia during the initial phase and later a macrocytic anaemia, heterophilia and slight monocytosis by 66th day post infection. The infected birds lost considerable amount of their body weight. In layers there was a great delay in sexual maturity and poor feed efficiency as indicated by greatly reduced egg production. The percentage of establishment of worms in these experiments were found to be inversely proportional to the number of juveniles administered. The pathological changes in the affected proventriculi indicated an acute inflammation during the invasive phase of juveniles, followed by a chronic reaction which by 55th day post infection was well established indicating the development of a host – parasite balance towards the later stages of infection. Among the blood changes in monospecific A. spiralis infection, eosinophilia was evident initially followed by a marked leucopenia and development of a macrocytic hypochromic anaemia. Other effects due to parasitism were, delayed maturity, reduced rate of egg production, poor feed efficiency, loss of weight, emaciation and a mortality rate of 25% in chicks. The gross pathological changes in Acuariasis included the appearance of an irregular whitish patch on the serosa and formation of nodular growths in the mucosa which in heavy infections occupy the whole of the mucous membrane. Juveniles of A. spiralis were found to invade the compound glands in very heavy infections. The microscopic changes indicate a severe acute inflammation during the initial stages. Later as the disease became chronic pedunculated fibro – adenamatoid growths were evident on the mucous membrane. In dispecific infections with T. mohtedai and A. spiralis the haematological changes observed were eosinophilia during the early stages followed by a l eucopenia and heterophilia. As the disease progressed a macrocytic hypochromic anaemia developed. There was a great decrease in the live body weight of the infected birds. A mortality of 33.33% were observed in chicks with heavy infection. In layers the sexual maturity was delayed and egg production was greatly suppressed with consequent poor feed utilization. The gross and microscopic changes found in the affected proventriculi indicated a combination of lesions observed under monospecific infections of both the parasites. The results obtained show that the loss due to morbidity (mainly as a result of decreased body weight and reduced rate of egg production) was considerable. These facts indicate that both T. mohtedai and A. spiralis are economically important.